Effect of Age at Menarche on The Risk of Occurrence of Cardiovascular Adversities Among A Tribal North Indian Population - Khan, Simi; Thakur, Sunil K; Saraswathy, K N; P, Sachdeva M (Cardiology and Cardiovascular Medicine, 2017)
Background: The beginning of menarche, an important phenomenon of a female’s life and is associated with the development of various physiological and metabolic changes. Innumerable studies have shown a positive association of early menarche with development of cardio metabolic risk factors. WHO has also re-established that till 2015 the highest number of mortality and morbidity in India will be due to CVDs. The present study deals with understanding the association, if any, between the age at menarche and an increase in cardiovascular adversities among the Gaddis of Himachal Pradesh and further establishing that which group (early, normal or late menarche) is a better determinant of the same. Methods: This study is cross sectional household based study, including 317 ever married Gaddi women aged 25-70 years from higher altitude Himachal Pradesh’s two districts viz. Chamba and Kangra.. Data pertaining to demographic, reproductive, anthropometric, physiological and biochemical variables were collected from these women. They were further divided into three categories based on their age at menarche viz, early, normal and late and characterized for cardio-metabolic risk factors. Statistical analysis was done using SPSS version 16.0. Results: The mean age at menarche of the present population was observed to be 15.23 years, which is towards the higher side of the normal range. Also the number of females falling under the late menarcheal group is higher and closer to 75%. BMI and abdominal obesity are found to be significantly increased in females with early menarche. The early menarcheal group also has a significantly higher percentage of hyperglycemic individuals. Both hypertensives and pre hypertensives are increased in the late menarcheal group wherein pre hypertensives are significantly increased. The mean values of other lipid parameters (TC, TG, LDL